Association of bodyweight loss with changes in lipids, blood pressure, and fasting serum glucose following tirzepatide treatment in Japanese participants with type 2 diabetes: A post hoc analysis of the SURPASS J‐mono trial - Hanaka Mimura; Tomonori Oura; Rina Chin; Masakazu Takeuchi; Kazuya Fujihara; Hirohito Sone (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction In the SURPASS J‐mono trial, tirzepatide demonstrated significant improvements in bodyweight and several metabolic parameters in Japanese participants with type 2 diabetes. This post hoc analysis evaluated the potential relationships between weight loss and metabolic improvements in SURPASS J‐mono. Materials and Methods Metabolic parameter data from tirzepatide‐treated participants were analyzed by weight loss subgroups and compared to dulaglutide 0.75 mg. Correlations between changes from baseline to week 52 in weight loss and each metabolic parameter were assessed; Pearson correlation coefficients were derived. Mediation analyses were conducted to evaluate weight loss‐associated and ‐unassociated effects of tirzepatide vs dulaglutide 0.75 mg. Results This analysis included 548 participants (tirzepatide: n = 411, dulaglutide: n = 137). Weight loss subgroups showed greater improvement in metabolic parameters with greater bodyweight loss. Significant (P < 0.05) but weak correlations between changes in bodyweight and triglycerides (r = 0.18–0.25), high‐density lipoprotein cholesterol (r = −0.37 to −0.29), and systolic blood pressure (r = 0.19–0.41) were observed across treatment groups; in diastolic blood pressure in the tirzepatide 5‐mg (r = 0.28), pooled tirzepatide (r = 0.20), and dulaglutide 0.75‐mg (r = 0.23) groups; and in fasting serum glucose in the dulaglutide 0.75‐mg (r = 0.18) and pooled tirzepatide (r = 0.13) groups. Weight loss was associated with treatment differences between tirzepatide and dulaglutide 0.75 mg to varying degrees across metabolic parameters, with improvements in fasting serum glucose having the lowest association with weight loss (36.6%–43.5%). Conclusions In this post hoc analysis, non‐glycemic and glycemic parameter improvements appeared differentially associated with weight loss, suggesting both weight loss‐associated and ‐unassociated effects of tirzepatide.